Heavenly bodies: cult treasures & spectacular saints from the catacombs - Koudounaris, Paul (Thames and Hudson, 2013)
This book is the chronicle of a group of extraordinary skeletons discovered in the Roman Catacombs in the late sixteenth century. Largely anonymous, they were nevertheless held to be the remains of Early Christian martyrs, and treated as sacred. Sent to Catholic churches and religious houses in German-speaking Europe to replace holy relics that had been destroyed in the wake of the Protestant Reformation, the skeletons were carefully reassembled, and richly adorned with jewels and precious costumes. They became the centre of spiritual life for many communities, yet as time passed, faith in them wavered and they were cast out as imposters, as the Catholic Church turned its back on what was once one of its treasures. This is a story that until now has been left out of the pages of both art and religious histories